Spindle Cell Lesions of the Breast: A Diagnostic Algorithm - Ni, Yunbi; Tse, Gary M. (Archives of pathology & laboratory medicine (1976), 2023)
Spindle cell lesions of the breast represent a broad spectrum of entities, ranging from nonneoplastic reactive conditions to high-grade malignant tumors. The wide range makes breast spindle cell lesions a diagnostic pitfall. To review the classification of spindle cell lesions of the breast, including clinical features, morphologic characteristics, and the role of immunohistochemistry as well as molecular tools in assisting the differential diagnosis. A diagnostic algorithm will be proposed. Literature and personal experience are the sources for this study. Spindle cell lesions of the breast can be classified as biphasic or monophasic, with the former including both spindle cell and epithelial components, and the latter including only spindle cell elements. Each category is further subclassified as low or high grade. In the biphasic low-grade group, fibroadenoma and benign phyllodes tumor are the most common lesions. Other uncommon lesions include hamartoma, adenomyoepithelioma, and pseudoangiomatous stromal hyperplasia. In the biphasic high-grade group, borderline/malignant phyllodes tumor and biphasic metaplastic carcinoma are the main lesions to consider. In the monophasic low-grade group, reactive spindle cell nodule, nodular fasciitis, myofibroblastoma, fibromatosis, and fibromatosis-like metaplastic carcinoma have to be considered. In the monophasic high-grade group, the possible lesions are monophasic spindle cell metaplastic carcinoma, primary breast sarcoma, and metastases. Awareness of the clinical history and careful evaluation of any epithelial differentiation (with a large immunohistochemical panel) are crucial in the distinction.